Survey on carbon dioxide emission from internal combustion engines - Mohamad Khairul Hadi, Che Mohamad Khalib (2008)
This research is conducted to study about the carbon dioxide emission from passenger car. Passenger car is one of the largest shares of internal combustion engine vehicle on the road today. Therefore, they are also responsible for a large proportion of the environmental pollution such as the greenhouse gas emission. On this study four different ages of cars will be tested experimentally for their carbon dioxide emission using the universal emission analyzer machine. From the experiment result, carbon dioxide emission index is then being proposed. Using the data from the Pahang Road and Transport Department (JPJ), the carbon dioxide emission index for different car age in Pahang state is then being determined. This research also will determine some of the solutions to reduce the carbon dioxide emission from internal combustion engine. From this research it is clear that the age of the car play a significant role of carbon dioxide emitted. Generally, the older the car emits more carbon dioxide compare to the newer car for the same time of use. There are some possible solutions to reduce this emission as being proposed by some other researcher. Policy implementation and alternative fuel vehicles are just some of these possible solutions.